Creative Marketing and its role in Revitalizing Tourism Marketing : A Field Study of Companies, Travel and Tourism Agencies in Erbil Governorate - Nori Agha, Dr. Afaf Y. (Mitanni Journal of Humanitarian Sciences, 2023)
Abstract The aim of this research is to identify the concepts of creative marketing since the tourism industry and its products are subject to change and innovation reflecting the continuous changing desires and needs of tourists. There are a number of challenges that face tourism marketing both within the tourism enterprises and outside it, relating to economic and political instabilities and mishaps in addition to the challenges brought forward by advanced technological that affect both products and services and therefore all methods and strategies should be adopted in order to face competition and achieve competitive advantage. The research is comprised of theoretical investigation and fieldwork in order to find a prospective strategy to follow for tourism marketing in the Kurdistan Region. A random sampling of companies and travel agencies were taken in Erbil governorate. The question of the research is to find out the feasibility of implementing creative marketing in a company, or a travel agency that deal with tourism in Erbil for enhancing tourism marketing. Therefore, the research dealt with the top terminologies in the field of innovation in order to avoid confusion between innovation, creation, invention and renewal. It also dealt with creativity in general and creativity in marketing in particular, and samples from marketing creativity in the field of tourism and its requirements. The field work was comprised of two parts, the first part included field visits and interviews with tourism marketing personnel, in which the samples where from the private sector. Likewise, there were field visits to the board of tourism in the Kurdistan Region, and many in person meetings took place with a number of managers who are directly or indirectly involved in tourism marketing. The research arrived at a number of conclusions and recommendations, the most significant of which is that creative tourism marketing has become a demanding necessity because it aims at discovering the desires and the latent needs of tourists that are not realized by them or those that tourists are unable to express or unwilling to express. As for the conventional form of tourism the needs and the desires are clear in the minds of the tourists and they are willing to articulate them easily. The most important recommendations deal with the fact that the personnel in the field of tourism marketing, be it companies or travel agencies in the Kurdistan region, are in dire need of developmental programs that would further empower them to work in the field of marketing, and they are in need of advanced and up-to-date vocational skills in creative marketing. There is also the need to review the form that is used to offer licenses for the profession of tourism on the part of companies, travel agencies and travel offices, especially as far as experience and prequalification are concerned so as the Kurdistan Region would meet the international standard criteria for tourism. Key words: creative marketing, tourism and travel (company, agency, office), Erbil